2017
DOI: 10.1177/2054270417739778
|View full text |Cite
|
Sign up to set email alerts
|

Same features, different diagnosis: A case of ilio-iliac arteriovenous fistula presenting as decompensated heart failure

Abstract: In case of high output cardiac failure, an arteriovenous fistula should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…7,8 A variety of symptoms appear depending on the size and location of AVF. 9,10 Given that the fistula of ilio-iliac segment was away from aorta and IVC, its blood flow volume is smaller than aortocaval fistula. Thus, an ilio-iliac AVF presenting with systematic symptoms is rare.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7,8 A variety of symptoms appear depending on the size and location of AVF. 9,10 Given that the fistula of ilio-iliac segment was away from aorta and IVC, its blood flow volume is smaller than aortocaval fistula. Thus, an ilio-iliac AVF presenting with systematic symptoms is rare.…”
Section: Discussionmentioning
confidence: 99%
“…1,11 We searched literatures since 1999 by using PubMed, and found only two patients with ilio-iliac AVF presenting multi-organ dysfunction. 10,12 However, both of them had an extensive fistula orifice, which demonstrated that ilio-iliac AVF may be fatal with specifically unfavorable anatomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations